Analysis of Factors and the Role of Posyandu Elderly in Influencing the Elderly to Come to Health Services - Ni Putu Indah Rosita; I Wayan Septa Wijaya; Ni Luh Ayu Citra Mutiarahati (Universitas Ibn Khaldun Bogor, 2023)
The increase in the elderly population presents many challenges in the field of health services. The elderly population influences so many aspects of people's lives, one of which is the need for acute and long-term health care. Posyandu for the elderly is a forum for activities from the community and for the community which is supported by cross-sectoral collaboration, and the community health center provides technical support and guidance. Activities at the posyandu include preventive, promotive, curative, and rehabilitative activities. The success of health services for the elderly in the form of promotive, preventive, and curative efforts through means and facilities such as posyandu for the elderly and community health centers is determined to a large extent by the behavior and perspective of the elderly themselves which shape their attitudes and actions in selecting services. So there will be many factors that influence elderly people coming to health services. This research aims to obtain information about the factors and role of elderly posyandu in influencing elderly visits to health service centers. This article method uses a literature review design, namely the researcher reviews, summarizes, and writes down thoughts on several pieces of literature such as articles. The results of this literature review show that factors such as elderly posyandu, finances, social support, knowledge, and physical accessibility influence elderly visits to health services. Understanding these factors can help in designing interventions aimed at improving older adults' access to necessary health services.